Synthesis and Reactivity of NHC‐Stabilized Iron(II)–Mesityl Complexes. Issue 19 (23rd May 2017) - Schneider, Heidi; Schmidt, David; Eichhöfer, Andreas; Radius, Michael; Weigend, Florian; Radius, Udo
Abstract : We present the synthesis of a series of NHC‐stabilized iron(II) complexes of the type [Fe(NHC)2 Mes2 ] and [Fe(NHC)Mes2 ], starting from [Fe2 Mes4 ] and the NHC. Depending on the steric demand of the NHC used, tetrahedral [Fe(Me2 Im)2 Mes2 ]1 and [Fe(Me i PrIm)2 Mes2 ]2 , square‐planar trans ‐[Fe( i Pr2 Im)2 Mes2 ]3 , or trigonal‐planar [Fe(R2 Im)Mes2 ]; R = t Bu6, Dipp7, Dipp2 H2 8 complexes were isolated. Three‐coordinate complexes [Fe(R2 Im)Mes2 ] (R = Me4, i Pr5 ) of smaller carbenes were synthesized via ligand exchange of [Fe(NHC)2 Mes2 ] and [Fe2 Mes4 ]. The reactivity of trans ‐[Fe( i Pr2 Im)2 Mes2 ]3 towards small molecules and element–hydrogen compounds was investigated. The reaction of3 and2 with dioxygen led to the tetrameric‐cluster complexes [Fe(R2 Im)(OMes)(µ 2 ‐O)4 ]9 and10 (R = i Pr9, Me10 ). The reaction of3 with CO afforded [Fe( i Pr2 Im)2 (CO)3 ]11 . Reactions of3 with E–H compounds (E = O, S, N, P, Sn), with substitution of the mesityl ligands, produced the complexes [Fe( i Pr2 Im)2 (O t Bu)2 ]12, [Fe( i Pr2 Im)2 (OPh)2 ]13, [Fe( i Pr2 Im)2 (SPh)2 ]14, [Fe( i Pr2 Im)2 (NHPh)2 ]15, cis ‐[Fe( i Pr2 Im)2 o ‐C6 H4 (NH)2 ]16, [Fe( i Pr2 Im)2 (PHPh)2 ]17, [Fe( i Pr2 Im)2 (PPh2 )2 ]18, trans ‐[Fe(Me2 Im)2 (Sn n Bu3 )2 ]19, and trans ‐[Fe( i Pr2 Im)2 (Sn n Bu3 )2 ]20 . The complexes16, 17, 19, and20 adopt square‐planar structures. The reaction of3 with phenylsilane afforded crystallographically characterized [Fe( i Pr2 Im)2 (µ 2 ‐H)3 (SiPh2 H)SiH2 ( i Pr2 Im)]21 . Abstract : The synthesis of tetrahedral, square‐planar, and trigonal‐planar complexes of the type [Fe(NHC)2 Mes2 ] and [Fe(NHC)2 Mes2 ], as well as the reactivity of the square‐planar complex trans ‐[Fe( i Pr2 Im)2 Mes2 ] towards small molecules and element–hydrogen compounds is presented.